Biomechanics of healthy subjects during exercise on a simulated vibration isolation and stabilization system - Blocker, Abby; Lostroscio, Kaitlin; Carey, Stephanie L. (Life sciences in space research, 2022)
•Future space missions will include redesigned astronaut exercise hardware.•Designs must isolate exercise-induced vibrations and allow for proper joint loading.•Simulation was used to study exercise performance under multiple parameters.•Platform movement shown as a viable option to isolating exercise-induced vibrations. With long-term space flights being planned for the Moon and Mars, proper countermeasures must be taken to facilitate human health in microgravity environments. Exercise is a vital countermeasure used to prevent bone and muscle loss, among other health interests. Future exploration missions encourage creating an exercise device that is both compact and can be used to properly execute exercise by the astronauts. Current design considerations include interfacing an exercise device with a vibration isolation and stabilization (VIS) system, which is necessary for protecting the spacecraft and sensitive experiments from harmful vibrations developed during repetitive exercise. This human factor study assesses the feasibility of a VIS system exercise device by using the Computer Assistive Rehabilitation Environment (CAREN) to simulate characteristics of the system. The CAREN includes a 6 degree of freedom (DOF) platform, force plates and a motion capture system. An algorithm was developed using the D-Flow software to move the platform in 1 and 2 DOF sinusoidal responses. Multiple sinusoidal frequencies for platform motion during subject exercise were evaluated. Four subjects completed squat and row exercises on the CAREN while their motion was recorded. Kinematic and kinetic data were collected from each subject. Trials were executed with 1-2 DOF motion in heave and pitch. Results conclude that subjects completed exercises with adequate range of motion (ROM) and ground reaction forces (GRF) during each trial. Certain environments, such as movement at a slower frequency (0.10 Hz) and movement of heave and pitch at differing frequencies, caused loss of balance indicated by grabbing of the handrail in some subjects and difficulty in synchronization between the subjects and the platform. This indicates that VIS system design should focus on frequency of movements centering around subjects’ natural exercise frequencies if possible. This study serves as a proof of concept for using CAREN and programming tool D-Flow to simulate platform movement on VIS system design. Further experimentation will test more detailed designs, including active and passive systems that will move based on real-time subject data.